Distinguishing between benign and malignant breast lesions using diffusion weighted imaging and intravoxel incoherent motion: A systematic review and meta-analysis. Issue 141 (August 2021) - Ma, Weili; Mao, Jiwei; Wang, Ting; Huang, Yanan; Zhao, Zhen Hua
Highlights: The highest performing parameter for IVIM was tissue diffusivity(D), DWI and IVIM have high sensitivity and specificity in the differential diagnosis of breast lesions. DWI was comparable to D with effects of perfusion excluded. There was no significant differences between studies on different max b<1000 vs. b=1000 vs. b>1000, 1.5 field strength vs.3.0 field strength. Abstract: Purpose: We sought to evaluate the diagnostic performance of diffusion weighted imaging (DWI) and intravoxel incoherent motion (IVIM) for distinguishing between benign and malignant breast tumors by performing a meta-analysis. Methods: We comprehensively searched the electronic databases PubMed and Embase from January 2000 to April 2020 for studies in English. Studies were included if they reported the sensitivity and specificity for identifying benign and malignant breast lesions using DWI or IVIM. Studies were reviewed according to QUADAS-2. The data inhomogeneity and publication bias were also assessed. In order to explore the influence of different field strengths and different b values on diagnostic efficiency, we conducted subgroup analysis. Results: We analyzed 79 studies, which included a total of 6294 patients with 4091 malignant lesions and 2793 benign lesions. Overall, the pooled sensitivity and specificity of ADC for detecting malignant breast tumors were 0.87 (0.86–0.88) and 0.80 (0.78–0.81), respectively. The PLR was 5.09 (4.16–6.24); the NLR was 0.15 (0.13–0.18); and the DOR was 38.95 (28.87–52.54). The AUC value was 0.9297. The highest performing parameter for IVIM was tissue diffusivity (D), and the pooled sensitivity and specificity was 0.85 (0.82–0.88) and 0.87(0.83–0.90), respectively; the PLR was 5.65 (3.91–8.18); the NLR was 0.17 (0.12–0.26); and the DOR was 38.44 (23.57–62.69). The AUC value was 0.9265. Most of parameters demonstrated considerable statistically significant heterogeneity (P < 0.05, I 2 >50 %) except the pooled DOR, PLR of D and the pooled DOR and NLR of D*. Conclusions: Our meta-analysis indicated that DWI and IVIM had high sensitivity and specificity in the differential diagnosis of breast lesions; and compared with DWI, IVIM could not further increase the diagnostic performance. There was no significant difference in diagnostic accuracy.